Small bowel gastrointestinal stromal tumours and ampullary cancer in Type 1 neurofibromatosis - Behranwala, Kasim A (BioMed Central, 2004)
BACKGROUND: Type 1 neurofibromatosis (NF-1) is an autosomal dominant disorder with variable penetrance; approximately 50% of cases present as new mutations CASE REPORT: We report a case of a 56 year-old man with Von Recklinghausen's disease, carcinoma of the ampulla of Vater and incidental benign gastrointestinal stromal tumours of the jejunum. CONCLUSIONS: Coexistence between ampullary carcinoid, ectopic pancreatic tissue in the jejunum and neurofibroma of the jejunum in NF-1 has been previously described however; the association of synchronous carcinoma of the ampulla of Vater and gastrointestinal stromal tumour of the jejunum in NF-1 has not been previously reported.